MILP model for optimal operation of biomass facility treatment for efficient oil palm biomass management - Loon, Lim Kai; Shukery, Mohamad Firdza; Hashim, Norhashila (Springer, 2024)
Malaysia has experienced a significant increase in revenue from palm oil production over the years, resulting in a substantial quantity of biomass during the extraction of crude palm oil. To promote sustainability in the oil palm industry, it is essential to utilize the generated oil palm biomass effectively, aiming for a zero-waste approach. The biomass conversion not only generates additional revenue but also contributes to industry sustainability and environmental friendliness. However, factors such as biomass availability, conversion technologies, product demand, and time constraints must be carefully considered. The objective of this study is to analyze the potential conversion of oil palm biomass into bio-based products using a mixed-integer linear programming (MILP) model. The model was optimized using the General Algebraic Modelling System (GAMS) software version 40.1, which considers critical factors, including biomass availability, conversion technologies, product demand, and time considerations. The study findings indicate that the generation of electricity and paper pulping offer a favorable return on investment and short payback periods, despite their initial high startup costs. In the case study of Kota Tinggi, electricity generation yielded the highest profit (RM 25,856,806.14), followed by paper pulping (RM 10,708,378.18), and fertilizer composting (RM 142,053.51). In contrast, 227,0538.4 kWh of electricity can be generated, amounting to 49.50 million Ringgit Malaysia, and 5,063.6 tons of bio-fertilizer, totaling 3.13 million Ringgit Malaysia. In conclusion, this model facilitates the selection of optimized profitable products, a key focus of the study, and helps determine the most profitable approach for utilizing oil palm biomass.